Family Support and Social Functions of Schizophrenia Patient - Dhina Widayati; Eko Arik Susmiatin; Fenti Yana Priandana (STIKES dan AKZI Karya Husada Kediri, 2023)
Schizophrenia is a mental disorder characterized by decreased mental function and changes in cognitive, affective and psychomotor which can create obstacles in carrying out social functions for individuals. One of the factors that can improve social functioning in people with schizophrenia is family support. The purpose of this study was to determine the relationship between family support and the social functioning of schizophrenics in the community at the Campurdarat Health Center in Tulungagung. The research design used is correlation with a cross sectional approach. The sample size is 31 respondents obtained using purposive sampling. The measuring tool used for independent variables is a closed model family support questionnaire and the dependent variable uses interviews and observations of the social functioning of schizophrenics. The data obtained were analyzed and tested with Spearman Rho. The results showed that almost half (45.2%) of the respondents had family support in the good category and almost half of the respondents (48.4%) had social functions in the good category. The results of the Spearman rho test obtained a value of p = 0.001 and r of 0.94. This shows that there is a relationship between family support and social functioning of schziophrenics with a very strong level of relationship in a positive direction. This means that the better the family support, the better the social function. This is because by getting family support, people with schizophrenia feel not alone, needed, there is hope, useful and various other positive feelings. It was concluded that family support is effective for improving the social functioning of schizophrenics. It is recommended that health workers improve the provision of mental health services by forming support groups, forming community groups concerned with mental health, and forming self-help groups.